2008
DOI: 10.1111/j.1743-6109.2007.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

A Passion for Castration: Characterizing Men Who Are Fascinated with Castration, but Have Not Been Castrated

Abstract: Introduction A number of men have extreme castration ideations. Many only fantasize about castration; others actualize their fantasies. Aims We wish to identify factors that distinguish those who merely fantasize about being castrated from those who are at the greatest risk of genital mutilation. Methods Seven hundred thirty-one individuals, who were not cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 7 publications
(40 reference statements)
4
40
0
Order By: Relevance
“…Consistent with the data in Roberts et al (2008), we found significant differences between the groups concerning their selfidentified gender. Not surprisingly, those who had already obtained genital ablation aligned with a "eunuch" or "third gender" identity more often than those who had not yet been castrated.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the data in Roberts et al (2008), we found significant differences between the groups concerning their selfidentified gender. Not surprisingly, those who had already obtained genital ablation aligned with a "eunuch" or "third gender" identity more often than those who had not yet been castrated.…”
Section: Discussionsupporting
confidence: 92%
“…While more "wannabes" indicated that their desire to be castrated was driven by sexual fantasies, the major motivation for genital ablation among men who had been castrated and/or penectomized was libido control. Overall, our results support the conclusions of Roberts et al (2008) and bolster them with a much larger sample size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reasonable understanding of the effects of contemplated medical treatments and ability to adhere to a therapeutic regimen also should be assessed Meyer et al, 2001) consistent with usual principles of decision-making capacity and informed consent. Assessment of co-occurring mental illness, particularly psychopathology that may influence the transgender presentation or that may be mistaken for transgender (e.g., Skoptic syndrome, in which a person is preoccupied with or engages in genital self-mutilation, such as castration, penectomy or clitoridectomy) and psychotic disorders, etc., is paramount (Hembree et al, 2009;Roberts, Brett, Johnson, & Wassersug, 2008).…”
Section: Psychotherapy and Mental Health Supportmentioning
confidence: 98%